Atopia consumível do patrimônio mundial : Sintra como lugar de consumo cultural - Feitosa, Allan Rafael Veiga (2018)
In 1995, UNESCO designated the "Cultural Landscape of Sintra-PCS" (Portugal) as World Heritage, the first item in the world to be directly registered in this category. He did it, punctuating the characteristics and singular elements of that spatiality, especially the strong relation, considered harmonious, of the man with the environment, witnessed in diverse sociocultural contexts, by different peoples, from prehistory to the twentieth century, entailing a tangle of socio-cultural dynamics that gave Sintra senses of mysticism and magic, composing a sociocultural whole that we call "Aura of Sintra"; part of the 19th-century foundation of Portuguese Romanticism, represented in the "Pena Palace", a unique and original architectural style that, for many, influenced the landscape architecture of part of Europe. In the interaction of the characters of Portuguese Romanticism with Sintra, there was a sense of understanding about that spatiality that, philosophically, referred to a topos, in an Aristotelian sense, and of "place", of sociological character. As we analyze the discourse of the UN / UNESCO, such a seal should not be seen as just another mechanism of cultural safeguard, this titulación constitutes as part of the actions that permeate the mission of the entity; of "promoting a culture of peace among peoples," entrusting these patrimonies with a task of being a kind of "living testimony ... that no culture has grown in isolation, and that diversity is a force. .] to seek in our diversity the ties that unite humanity. "(UNESCO), drawing from them a patrimonial quality, so to speak, humanitarian, aiming at the contact, in a certain strangeness, of the visitor and the other visited. Although the proposal has a character of "humanitarian resource", based on conceptual and philosophical premises adjacent to the entity, the market approach in this type of equity is quite strong and recurrent, using the prestige of the institution and the characteristics of the patrimonial items. In addition to the questions and noises about a certain "universal universal value", it is evident that the "world patrimony" is, inescapably, a "patrimonialisation process", subject to economic investments already observed in other processes. In this sense, we understand that while the patrimonies of humanity are discursively clad in a "culture of peace promotion", inclined to a sense of showing that all peoples would have something cultural product of an amalgam of "human community" in addition to the particularities that affirm and delimit them, enabling the perception and understanding of otherness, in a kind of "ethics of otherness" in the sense of Emmanuel Lévinas (2010), this proposal has had its effects discussed, much as a function of the commitment of agents in a "consumption logic", on the basis of "cultural consumption" and "mass tourism", tending to blur the cultural differences ("negativities") that conform alterities towards a "positivity" flow, allowing a better condition for the exotic consumption of the "Aura of Sintra", subtracting, to a great extent, the relational experience with what Byung-Chul Han calls " immunology of the other atopic, "ie, the" negativity of the other, "configuring Sintra in what we understand as a sort of" place of equals, "including in a stream of" positivity "the" negativities of the other atopic "in a process we call "Consumable World Heritage Atopy". Since "ethics of otherness" is an observable foundation in the "mission" of UNESCO, it is necessary to establish a relation of the self to the other; a relation in a very specific context of the other, in which the self can, in face-to-face contact with the other, apprehend it, endowed with a search posture to relate and perceive its self with this other, in terms of otherness. Thus, we discuss the way and the extent to which the premises and foundations of UNESCO within the framework of the PCS have relevance and practical effect, developing a thesis that points to the PCS as a resource of humanitarian foundation heavily prepared for cultural consumption, with contradictions between the purposes of the entity and the market practices that harm and detract from the conformation of alterities.